Pengembangan Teknik Food Plating terhadap Peningkatan Kepuasan Konsumen: Studi Kasus Balek Kampoeng Cafe And Resto - Shakirah Shakirah; Alip Suroto; Salam Setiawan (Yayasan Literasi Sains Indonesia, 2025)
This research aims to examine the influence of food plating techniques on consumer satisfaction at Balek Kampoeng Café and Resto. In the modern culinary industry, food presentation plays a crucial role in shaping taste perceptions, aesthetic value, and the overall dining experience. Visually appealing plating techniques are expected to create a positive impression on customers and foster customer loyalty. This study adopts a quantitative approach using a survey method and distributes questionnaires to 100 purposively selected respondents, who were visitors with prior experience dining at the restaurant and exposed to its food presentation. The research instrument was tested for both validity and reliability. All questionnaire items were found to be valid (r > 0.194) and demonstrated high reliability, with a Cronbach’s Alpha value of 0.901. Descriptive analysis revealed that consumers' perceptions of food plating and their satisfaction levels were both in the high category. The normality test showed that the data were normally distributed, with a significance value of p = 0.159. Furthermore, simple linear regression analysis indicated that food plating techniques had a significant effect on consumer satisfaction, with a significance level of 0.000 (< 0.05) and an R Square value of 0.660. This means that 66% of the variation in consumer satisfaction is explained by the variation in the food presentation techniques applied.